Exploring the Changes of Resistant Genes Expression in Groundnuts (Arachis Hypogea) In Response to Aspergillus Flavus Exposure at Seedling Stage - Okayo, Robert O.; Andika, Darius O.; Dida, Mathews M.; K’Otuto, George O.; Gichimu, Bernard M. (My University, 2020)
Aspergillus flavus infect groundnut seeds and produce secondary metabolites, aflatoxins. The aflatoxins are associated with various diseases in domestic animals and humans globally. Mitigating the aflatoxin contamination in crops through the development of cultivars tolerant to fungus colonization and aflatoxin contamination has been considered the most costeffective measure. This research was conducted to ascertain that the resistance genes identified in the previous transcriptome analysis were involved in groundnut defense mechanisms to A. flavus infection. Eight genes were selected for additional scrutiny through the real time PCR on a groundnut seedling at an interval of 2 days within a 7-day period. The results indicate a network of gene expression patterns in a sequential order in both resistance and susceptible lines at a seedling stage. The peak expression level per gene indicates the time gene action was crucial. We conclude that these genes are involved in groundnut resistance to A. flavus infection and provide important targets for the molecular marker screening.
Keywords: spergillus flavus; groundnuts; Real Time PCR; gene expression; aflatoxin; seedling